2008
DOI: 10.1111/j.1551-2916.2007.02253.x
|View full text |Cite
|
Sign up to set email alerts
|

Deposition Mechanism for Chemical Vapor Deposition of Zirconium Carbide Coatings

Abstract: Zirconium carbide (ZrC) coatings were fabricated by chemical vapor deposition (CVD) using ZrCl4, CH4/C3H6, and H2 as precursors. Both thermodynamic calculation results and the film compositions at different temperatures indicated that zirconium and carbon deposited separately during the CVD process. The ZrC deposition rates were measured for CH4 or C3H6 as carbon sources at different temperatures based on coating thickness. The activation energies for ZrC deposition demonstrated that the CVD ZrC process is con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 22 publications
4
50
0
Order By: Relevance
“…According to previous experimental and theoretical results on the deposition of ZrC [15,16] and SiC [21,22], the ratio of reactant gases is critical in the synthesis process. To facilitate the calculation, the relationship between ˛, ˇ and the production of condensedphases (ZrC and C) was firstly illustrated.…”
Section: Influence Of Gas Flow Ratementioning
confidence: 94%
See 1 more Smart Citation
“…According to previous experimental and theoretical results on the deposition of ZrC [15,16] and SiC [21,22], the ratio of reactant gases is critical in the synthesis process. To facilitate the calculation, the relationship between ˛, ˇ and the production of condensedphases (ZrC and C) was firstly illustrated.…”
Section: Influence Of Gas Flow Ratementioning
confidence: 94%
“…Several studies reported the CVD of zirconium carbide and carbon-zirconium carbide alloys [10][11][12][13][14][15][16][17][18]. The ZrC coatings are generally synthesized by zirconium halide [11,12] and hydrocarbons, such as CH 4 and C 3 H 6 [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of free carbon in ZrC with increase deposition temperatures was also reported by Wang et al ( 2008). The increase in carbon content may be attributed to the differences in the decomposition rates of methane and ZrCl4 as the temperature in the reaction zone is increased.…”
Section: Design and Fabrication Of A Chemical Vapour Deposition Systemmentioning
confidence: 67%
“…Zirconium tetrachloride (ZrCl 4 ) was used as zirconium source and propene (C 3 H 6 ) as carbon source. The deposition process can be described as [21]:…”
Section: Coating Preparationmentioning
confidence: 99%